Menakar Keberlanjutan Produksi Garam Rakyat di Surabaya - M. Imron Rosyidi; Budi Guntoro; Alia Bihrajihant Raya; Siti Khabir Rasyida Sa’idatin Ahmad (UNEJ e-Proceeding, 2018)
Produksi Garam Rakyat still supported the national salt most needs today, but one of the salt production center whose existence was threatening is the production of salt in Surabaya. Mantongan is a production workers rely on salt origin madura as spearhead production of salt in Surabaya, because the original society of Surabaya already do not want to work in the Agrokompleks sector (agriculture, fishing and animal husbandry, marines sector). As a result, many over land happened because the function of the land does not have an economic impact. Thats why, the existence of Produksi Garam Rakyat was treathning. This research aims to explain about the sustainability of the production of salt is seen from the perspective of cultural production arena. The method in tihis research is a critical approach to the qualitative eksplanatif. While the theory is the Social practice of Pierre Bourdieu on habitus and cultural production arena. The results of this research are the arena production of salt still shows the tendency of symbolic power. The skipper acted that way because they are pressured by market interests and wedged between the interests of the responsible of Mantongann or survive in the market. The Eight SDGs point show that the equality economy has not seen yet, so that the business was severely threatened.